Mesotherapy: From Historical Notes to Scientific Evidence and Future Prospects - Massimo Mammucari; Enrica Maggiori; Domenico Russo; Chiara Giorgio; Gianpaolo Ronconi; Paola E Ferrara; Flora Canzona; Luciano Antonaci; Bartolomeo Violo; Renato Vellucci; Domenico Rocco Mediati; Alberto Migliore; et al. (The Scientific World Journal)
Intradermal therapy, known as mesotherapy, is a technique used to inject a drug into the surface layer of the skin. In particular, it involves the use of a short needle to deposit the drug in the dermis. The intradermal microdeposit modulates the drug’s kinetics, slowing absorption and prolonging the local mechanism of action. It is successfully applied in the treatment of some forms of localized pain syndromes and other local clinical conditions. It could be suggested when a systemic drug-sparing effect is useful, when other therapies have failed (or cannot be used), and when it can synergize with other pharmacological or nonpharmacological therapies. Despite the lack of randomized clinical trials in some fields of application, a general consensus is also reached in nonpharmacological mechanism of action, the technique execution modalities, the scientific rationale to apply it in some indications, and the usefulness of the informed consent. The Italian Mesotherapy Society proposes this position paper to apply intradermal therapy based on scientific evidence and no longer on personal bias.